UBC-test use in the capacity of urinary marker of bladder cancer - S. I. Vintizenko; Ye. M. Slonimskaya; Ye. A. Usynin; S. L. Stukanov (Бюллетень сибирской медицины)
The enzyme immunoassay was used to evaluate diagnostic value of level of tumoral marker UBC at 54 patients with muscle invasive bladder cancer. The obtained data testify to possibility of use of the UBC-test for diagnostics primary bladder cancer, at monitoring for patients for revealing superficial and muscle invasive relapses after spent treatments. UBC it can be considered as the additional diagnostic marker, allowing to assume presence muscle invasive character of growth of a tumors, and also for an efficiency estimation neoadjuvant chemotherapy.